2001
DOI: 10.1002/1099-0682(200108)2001:8<2123::aid-ejic2123>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Arylthiazylamides with Internal and External Fluoro Electrophiles − Formation of Products with Unusual Structures

Abstract: The heteroatom reactivity of the title anions [as (Me 2 N) 3 S + and Cs + salts] toward both internal and external fluoro electrophiles has been investigated. The intramolecular nucleophilic cyclization of [ArNSN] − (as the cesium salts) bearing at least one ortho fluorine afforded 2,1,3-benzothiadiazoles (e. g. 2a,b), whereas intermolecular condensation with polyfluorinated pyridine and naphthalene afforded Ar−N=S=N−R with R = 4-Py F (4) and R = 2-Np F (8). Further interaction of [ArNSN] − with 4 or 8 proceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…An elegant reaction pathway was used to perform the synthesis of new, naphthalene‐containing, polyfluorinated derivative 78 , as shown in Scheme 72. It was show that intramolecular nucleophilic cyclization of arylthiazylamides bearing at least one ortho ‐fluorine offers a novel synthetic approach to BTD derivatives.…”
Section: Synthesis Chemical Properties Sulfur Extrusion and Mismentioning
confidence: 99%
“…An elegant reaction pathway was used to perform the synthesis of new, naphthalene‐containing, polyfluorinated derivative 78 , as shown in Scheme 72. It was show that intramolecular nucleophilic cyclization of arylthiazylamides bearing at least one ortho ‐fluorine offers a novel synthetic approach to BTD derivatives.…”
Section: Synthesis Chemical Properties Sulfur Extrusion and Mismentioning
confidence: 99%
“…73 N-Polyfluoroarylsulfur diimides 72 were proposed as intermediates in the synthesis of fused perfluoronaphthothiadiazole 73 (Scheme 34). 75,77 The cesium fluoride deprotects the sulfur diimide to afford a sulfur diimide anion, which can be regarded as a thiazylamide due to the short terminal SN bond. 78 This reacted with the fluorinated arene 74 to give an intermediate sulfur diimide, which subsequently undergoes intramolecular cyclisation to afford the fused thiadiazole 37.…”
Section: Scheme 32mentioning
confidence: 99%
“…Recently, 1:1 molecular complexes between octafluoronaphthalene and acyclic (Ar-N S N-Ar, Ar-N S NSiMe 3 ) and heterocyclic (7-methyl-2,1-benzothiazole) sulfur-nitrogen compounds featuring p-stacking interactions of the arene-polyfluoroarene type were synthesized [5,6]. Also, 2:1 inclusion complexes of the bicyclic sulfur-nitrogen compounds Ar-CN 5 S 3 (including polyfluorinated derivatives) and fluorocarbon and hydrocarbon aromatics were prepared, the inclusion is driven by arene-polyfluoroarene p-stacking interactions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Also, 2:1 inclusion complexes of the bicyclic sulfur-nitrogen compounds Ar-CN 5 S 3 (including polyfluorinated derivatives) and fluorocarbon and hydrocarbon aromatics were prepared, the inclusion is driven by arene-polyfluoroarene p-stacking interactions [4]. These investigations [4][5][6] showed that the molecular geometries of the sulfur-nitrogen derivatives were practically not affected by these interactions. In some cases, the co-crystals were much better suited for X-ray crystallography than the crystals of the individual compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation